Characterising adequacy or inadequacy of the borderline left ventricle: what tools can we use?*. (December 2015) - Kaplinski, Michelle; Cohen, Meryl S.
Abstract: Borderline left ventricle refers to a spectrum of left ventricular underdevelopment, typically associated with other cardiac anomalies. The left ventricle may be mildly hypoplastic, as is sometimes seen accompanying aortic coarctation, or it can be severely hypoplastic, as is seen in hypoplastic left heart syndrome. For patients with a borderline left ventricle that is at either extreme, the treatment decision is relatively straightforward. Those with the most severe form of left ventricle hypoplasia will require single ventricle palliation or cardiac transplantation, whereas those with the mildest form may not need any intervention. It is the management strategy of children that fall within the grey zone of the spectrum, which continues to be controversial and remains variable within and among different institutions. Cardiac diseases with associated left ventricle hypoplasia include critical aortic stenosis, mitral stenosis, coarctation of the aorta, arch hypoplasia, cor triatriatum, unbalanced common atrioventricular canal, Shone's complex, total anomalous pulmonary venous return, and complex conotruncal abnormalities. In this review, we will discuss the assessment and management of infants with borderline left ventricle with critical aortic stenosis or arch obstruction and associated mitral anomalies.